Periodontal Diseases and COVID-19: A Scoping Review - Basso, Lisa; Chacun, Doriane; Sy, Kadiatou; Grosgogeat, Brigitte; Gritsch, Kerstin (European Journal of Dentistry, 2021)
The aim of this scoping review was to present the existing literature regarding the relationship between periodontal diseases and coronavirus disease 2019 (COVID-19). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping review guidelines was followed. Articles were retrieved from PubMed/MEDLINE and Scopus databases and screened to include studies relating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or COVID-19 to periodontal cells and/or tissues and/or diseases. Twenty-five papers were included; consisting of six reviews, seven original articles, six short reports, four letters to the editor, one commentary, and one case report. The articles were allocated to three different topics: (i) hypotheses on the relationship between periodontal diseases and COVID-19; (ii) risk factors and comorbidities common to periodontitis and COVID-19; (iii) periodontal manifestations of COVID-19. Certain molecules (angiotensin-converting enzyme-2, furin, cathepsin, TMPRSS2...) that are found at a high level in periodontal tissues, particularly in patients with periodontitis, are involved in the mechanism of entry of SARS-CoV-2 into cells. Periodontopathic bacteria could also play a direct role in the mechanism of entry of SARS-CoV-2 by cleaving the S-protein, and the cytokines produced during periodontitis could add to the cytokine storm found in the severe forms of COVID-19. It thus appears that the treatment of periodontitis, which allows a reduction in periodontopathic bacteria and of the local and systemic inflammation state, could be part of a strategy to prevent the development of severe forms of COVID-19.
Keywords: coronavirus; risk factors; oral health; periodontitis